Association Between Null Genotypes of Glutathione S-Transferase M1 and T1 and Susceptibility to Systemic Lupus Erythematosus: A Meta-Analysis - Saadat, Mostafa (Scripta Medica, 2024)
Oxidative stress is involved in the development of systemic lupus erythematosus (SLE). It is well known that activity of the glutathione S-transferase superfamily has a protective effect against oxidative stress. Several studies have investigated the association between the GSTT1/GSTM1 polymorphisms and the risk of SLE with inconsistent results. The present meta-analysis was performed to investigate the association between susceptibility to SLE and the null genotypes of GSTT1 and GSTM1. Eligible publications were identified by searching several databases, 18 case-control studies with 2483 cases and 3643 controls met the inclusion criteria. The raw data of three reports have internal inconsistencies, therefore these studies were excluded from the final analysis. The results showed that the GSTM1 null genotype significantly increased the risk of SLE (OR = 1.17, 95 % CI: 1.03-1.32, p = 0.012) with no evidence of significant heterogeneity (Q = 14.53, df = 14, p = 0.411; I² = 3.4 %). The GSTT1 null genotype was not associated with the risk of SLE (OR = 0.94, 95 % CI: 0.80-1.10, p = 0.447). There was no evidence of heterogeneity between studies. The present study showed that the null genotype of GSTM1 was weakly associated with the risk of SLE.
Keywords: Glutathione S-transferases; GSTT1; GSTM1; Meta-analysis; SLE